Pengetahuan Ibu tentang Stimulasi Tumbuh Kembang Anak Usia 2 - 5 Tahun - Adiva Suci Chairunnisa; Samsualam; Wa Ode Sri Asnaniar; Nur Ilah Padhila; Sunarti (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
The influence of knowledge on child development is very important because mothers have sufficient knowledge and high education will pay more attention to the development of their children. On the other hand, if the mother does not pay attention to the child's development and does not provide stimulation to its development, the child will experience developmental delays. using a descriptive research design conducted at PAUD Kb Permata Bunda Nambo Village from July to August 2022. The determination of the sample was carried out using a total sampling technique with a sample size of 38 respondents. Data analysis using univariate analysis for frequency distribution. The results of this study indicate that the majority of respondents have less knowledge as many as 9 respondents (23.7) and 29 respondents with good knowledge (76.3). Consisting of good gross motor development as many as 28 people (73.7%) who lacked as many as 10 people (26.3%), good fine motor skills as many as 24 people (63.2%) who lacked as many as 14 people (36.8 %), good language development as many as 22 people (57.9%) who lacked as many as 16 people (42.1%), good social development of children as many as 32 people (84.2%) who lacked 6 people (15, 8%). The conclusion of this study most of the respondents have a low level of knowledge on gross motor development, fine motor development, language development and social development in children. Suggestions are expected for all mothers who have children 2-5 years to further increase knowledge about child development stimulation.